Implications of the COVID-19 pandemic on athletes, sports events, and mass gathering events: Review and recommendations - AlSamhori, J. F.; Alshrouf, M. A.; AlSamhori, A. R. F.; Alshadeedi, F. M.; Madi, A. S.; Alzoubi, O. (Sports Medicine and Health Science, 2023)
Since the coronavirus disease 19 (COVID-19), which caused several respiratory diseases, was formally declared a global pandemic by the World Health Organization (WHO) on March 11, 2020, it affected the lifestyle and health of athletes, both directly through cardiorespiratory and other health related effects, and indirectly as the pandemic has forced the suspension, postponement, or cancellation of most professional sporting events around the world. In this review, we explore the journey of athletes throughout the pandemic and during their return to their competitive routine. We also highlight potential pitfalls during the process and summarize the recommendations for the optimal return to sport participation. We further discuss the impact of the pandemic on the psychology of athletes, the variance between the team and individual athletes, and their ability to cope with the changes. Moreover, we specifically reviewed the pandemic impact on younger professional athletes in terms of mental and fitness health. Finally, we shaded light on the various impacts of mass gathering events and recommendations for managing upcoming events.